U.S. Political Corruption and Audit Fees - Jha, Anand; Kulchania, Manoj; Smith, Jared (The Accounting Review, 2021)
ABSTRACT Using data on corruption convictions from the U.S. Department of Justice, we find that auditors charge higher fees when a firm is headquartered in a more corrupt district. This result is robust to a wide range of time and location fixed effects, using capital city isolation as an instrument, and propensity score matching. We also find that, relative to those in non-corrupt districts, firms in corrupt districts are more likely to have weak internal controls and restate earnings, and that their auditors exert greater effort. This evidence suggests that auditing firms located in corrupt areas entails additional risk, which auditors price into fees. JEL Classifications: D73; G31; G34.